Spatial Variation in Water Quality Based on Biotic Indices Along Urban River Reservoir Continuum in Samarinda - Budiman Budiman; Khairunnisa Luthfiah; Fatmawati Patang (Jurnal Biologi Tropis, 2026)
The Karang Mumus River and Benanga Reservoir are water bodies that play a vital role in supporting ecological functions and meeting the socio-economic needs of urban dwellers of Samarinda. However, pressure from urban anthropogenic activities has caused a decline in water quality in both water bodies. This study aims to assess water quality along the Benanga Reservoir and Karang Mumus River using benthic macroinvertebrates as ecological indicators. Macroinvertebrate benthos sampling was conducted in March 2024 in the upper, middle, and lower reaches of the Karang Mumus River, as well as the Benanga Reservoir, which is the source of the river's water flow. Furthermore, water quality assessment along these waters was determined based on the importance value index (INP), Shannon-Wiener diversity (H'), evenness (E), and Simpson dominance (D), as well as biotic indices, namely BMWP-ASPT (Biological Monitoring Working Party-Average Score Per Taxon) and FBI (Family Biotic Index). The results of the study showed that Benanga Reservoir has a fairly high diversity (H' = 2.05), with a dominance of taxa sensitive to pollution, such as the Baetidae family, indicating relatively good water conditions. BMWP-ASPT and FBI values ​​indicate that the quality of Benanga Reservoir is relatively good. In contrast, the upstream, middle, and downstream segments of the Karang Mumus River showed a gradual decline in water quality. In the middle and downstream segments, the dominance of taxa tolerant of aquatic environmental pollution, such as Lestidae and Tubificidae, was observed, along with a high FBI value (9.49), indicating that the water is highly polluted with organic materials.